Localized field-aligned currents and 4-min TEC and ground magnetic oscillations during the 2015 eruption of Chile’s Calbuco volcano - Aoyama, Tadashi (2016)
The Calbuco volcano in southern Chile erupted on April 22, 2015. About 2 h after the first eruption, a Swarm satellite passed above the volcano and observed enhancement of small-amplitude (~0.5 nT) magnetic fluctuations with wave-packet structure which extends 15° in latitude. Similar wave packet is seen at the geomagnetic conjugate point of the volcano. Just after the eruption, geomagnetic fluctuations with the spectral peaks around the vertical acoustic resonance periods, 215 and 260 s, were also observed at Huancayo Geomagnetic Observatory located on the magnetic equator. Besides these observations, around 4-min, i.e., 175, 205 and 260 s, oscillations of total electron content (TEC) were observed at global positioning system stations near the volcano. The horizontal propagation velocity and the spatial scale of the TEC oscillation are estimated to be 720 m/s and 1600 km, respectively. These observations strongly suggest that the atmospheric waves induced by explosive volcanic eruption generate TEC variation and electric currents. The Swarm observation may be explained as a manifestation of their magnetic effects observed in the topside ionosphere.